Kurdish-Arabic Code-Switching in Nali’s Selected Poems - Abdulla , Luqman Abdulrahman (Zanco Journal of Human Sciences, 2021)
The present study aims at exploring Kurdish-Arabic code-switching in selected poems of Nali. Nali was a famous Kurdish classical poet. In his poems, Nali frequently swapped from Kurdish to Arabic. The researcher analyzes his poems from a sociolinguistic perspective. Therefore, the thrust of this paper is to clarify the role of this phenomenon in sociolinguistic, functional and structural aspects. The researcher has hypothesized that the sociolinguistic model of code-switching proposed by the American Linguist, Gumperz (1982) is applicable for the analysis of the phenomenon of code-switching in Nali’s poems. The study concluded that code-switching happens in multilingual society in conversation even in poems. The verses in which code-switching occurs are described as macaronic in literature. Another achievement is that macaronic poems of Nali were not the outcome of illiteracy or poor linguistic competence, on the contrary, they reflect his powerfulness in the use of his bilingualism and linguistic competence. Thus, code-switching is a positive point in his poems and adds to his rhetoric.